Identification of Single Nucleotide Polymorphism (SNP) in Exon 5 of the Prolactin Gene in Native Chickens - Rozi, Tapaul; Maskur, Maskur; Jan, Rahma; Kasip, Lalu Muhammad; Muhsinin, Muhammad (Jurnal Biologi Tropis, 2025)
The prolactin gene (PRL) in chickens is one of the genes that regulates broodiness and egg production in laying hens. Single Nucleotide Polymorphism (SNP) is a form of single nucleotide variation in the DNA base sequence at specific locations in the genome that can influence differences in quantitative traits in livestock. This study aimed to identify SNPs in the prolactin gene of native chickens. The research methods included DNA extraction, PCR amplification, and DNA sequence analysis for genotype determination of individuals. The results revealed four mutation points at positions g.8052 bp T>C, g.7886 T>A, g.7823 A>G, and g.8069 T>C. All mutation points in exon 5 were substitution mutations. Statistical analysis showed that all loci were polymorphic and the population was in Hardy–Weinberg equilibrium.